Analisis Material Kevlar Dengan Coating Polyurea Sebagai Bahan Pembuatan Sepatu Pdl Tni Untuk Medan Operasi Militer Di Sugapa, Intan Jaya, Papua - Sahirah Princka Riyanti; Sovian Aritonang (Rekayasa Material, Manufaktur dan Energi, 2026)
Sugapa District, Intan Jaya Regency, Papua, is a region prone to military conflict, with its highland, hilly topography and extreme climate. Temperatures can reach 9.2°C with high rainfall. These conditions demand robust, durable military equipment that provides maximum protection for Indonesian National Armed Forces (TNI) personnel engaged in military operations. One such area is Field Service Equipment (PDL) footwear. PDL footwear must meet the criteria for protection, high grip, abrasion resistance, and optimal insulation from temperature and water. However, the current standard TNI PDL footwear does not meet the criteria for the Sugapa theater of operations, Papua. This research was conducted to examine and characterize a Kevlar-based composite material with a polyurea coating as an innovative raw material for TNI PDL footwear. Kevlar is a material that has been proven to be superior anti-ballistic, with a very high tensile strength of approximately 3620 MPa and high resistance to impact and punctures. Furthermore, polyurea, an elastomer with a deformation elongation of 400-500%, is considered an appropriate material for enhancing the waterproof properties and chemical resistance of Kevlar. The research method used a systematic literature review to examine published research data on Kevlar, polyurea, military equipment, and the conditions in Sugapa District, Papua. Data analysis was conducted using a descriptive-qualitative method to address the urgent need for Kevlar-polyurea composite materials. The material analysis results showed that a Kevlar coating with a polyurea layer with a thickness variation of 0.2 mm on the front layer was the most optimal material configuration. This configuration provided the highest Ballistic Velocity Limit (Vbl) of 143.5 m/s, with a 58% increase in protection compared to plain Kevlar (90.8 m/s). Furthermore, the specific energy absorption efficiency also reached the highest value at 51.1 J.m2/g. The front-side coating has proven superior as a buffer layer, effectively absorbing impact energy and altering the fiber failure mode. In addition to the material used, the right outsole design is also crucial for slip control in the wet, muddy Sugapa operating terrain. The lightweight and flexible design demonstrates superior anti-slip performance. The combination of 0.2 mm Kevlar PU composite material with an optimal outsole design creates an effective surgical shoe in the Sugapa operating terrain.